ACTUALIZATION OF THE UKRAINE-CONCEPT IN THE ENGLISH-LANGUAGE OFFICIAL DISCOURSE OF THE EU - Olesya I. Yehorova; Vitalina S. Zaika (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
Nowadays, politics plays one of the most important roles in shaping social life of the country, its present and future. Political discourse has ceased to be something euphemistic and inaccessible to ordinary citizens. Political discourse has become the object of multidisciplinary research and political linguistics in particular since it is the platform for the interaction between the society and the authorities. Within the political discourse, a number of microdiscourses develop, one of which is the official political discourse of the EU which we regard as the environment for generation and actualization of political concepts and official political texts. The more attention drawn to Ukraine on its way to democratization and European integration, the more frequently Ukraine’s name appears in the EU legal texts and the statements of the EU officials. From the perspective of semantic and cognitive approach, this study considers the UKRAINE-concept and attempts at conceptual modeling of its structure based on the language material from the English-language official discourse of the EU. The relevance of the chosen topic is determined by its conformity with the dominant anthropocentric paradigm of modern linguistics and by overall importance of seeing the big picture of how Ukraine is conceptualized at the official level of the EU, what her gaps, gains, and goals are. Every conceptual picture of the world features universal and specific concepts. One of the specific linguistic and cultural concepts is the UKRAINE-concept. Within the semantic and cognitive approach, the concept is viewed as a three-layer structure consisting of notional, figuratively-perceptual and evaluative layers, each of them being relevant for concept carriers. In the course of research, cognitive features that determine the content of these main conceptual layers are identified. The conceptual features stored within the notional layer of the concept give reasons to think that Ukraine is primarily conceptualized in terms of its localization on the map of Europe. The figurativelyperceptive and evaluative layers store the sets of associations, images, and evaluations of the concept which are the results of experiential dealing with the denotatum. These are primarily coded in the forms of cognitive metaphors. Among the scope of cognitive metaphors through which Ukraine is conceptualized in the official English-language discourse of the EU anthropomorphic metaphors prevail. The evaluative layer features the cognitive traces of positive and negative evaluations of Ukraine. In political contexts, Ukraine is often associated with corruption, destabilized life and the country’s political and economic situation, military conflict. However, Ukraine is positively treated due to its potential of further development of Ukraine, through the belief in overcoming crisis and stabilizing the situation with the help of reforms suggested by the EU.